The Effect of Krill Oil and n-3 Polyunsaturated Fatty Acids on Human Osteosarcoma Cell Proliferation and Migration. - Xiao, S.; Tanalgo, P.; Bustos, M.; Dass, Crispin (2015)
Osteosarcoma (OS) is a neoplastic condition afflicting mostly the young, as the lesion usually occurs in areas of bone growth with tumour cells metastasising to the lungs in advanced disease. There is no real cure for the disease, with conventional drugs causing side-effects that decrease the quality of life of sufferers. Newer and safer drugs are needed, and one avenue is to use natural compounds that can stunt the growth of the tumour. In this study, two such biological entities were evaluated: krill oil and fish oil. Human OS cells were exposed to krill oil, fish oil, EPA and DHA in time-course assays lasting up to 72h. Krill oil inhibited 23, 50 and 64% of cell proliferation at 24, 48 and 72h respectively, while fish oil resulted in no significant changes although an increase was observed at 24h. Interestingly EPA and DHA promoted OS cell proliferation and migration in this neoplasia. The inhibitory effect of krill oil was comparable to 0.5 and 1µM doxorubicin, a commonly used clinical drug for OS treatment. These results indicate that krill oil may be used in combination with standard clinical practices to control primary tumour growth, and more importantly, metastasis.